Caracterização da transição de regimes na camada limite atmosférica noturna durante a ocorrência de drenagem - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The main goal of the work is to examine the transition of regimes in the CLE, during the occurrence of nights that presente drainage ﬂow. The drainage ﬂows evidenced in the terrestrial surfaces present their development at night, under clear sky conditions and low Wind speeds. Forth is reason, this phenomenon occurs under conditions in which the Atmospheric Boundary Layer is stable. In addition, drainage ﬂow sinclude a high variability of situations and cases, as the ﬂowin proximity to the surfasse is modulated by the slope of the terrain. In this study, winds peed, temperature and radiation data were analyzed at night for two distinct data sets. The ﬁrst dataset is the CASES-99, which includes data from eight three-dimensional sonic anemometers that operate in the main tower during the period of October 1999. The second, called the Experimental Site of Santa Maria, implemented in the Campus from the Federal University of Santa Maria, more speciﬁcally, located in na área of 24 há of the Pampa Biome, analyzes the data collected by the micrometeorological tower for the month of April of the year 2021. The results predominantly show that the characterization of drainage ﬂows, as well as the transition of regimes in these conditions, it is possible since it was veriﬁed that katabatic ﬂows occur on nights with higher radiative divergence and with the incidence of light wind, with values lower than 4 m s_1. In the same way, a high temperature gradiente is established between the surfasse and the layers of air above it. As the temperature gradiente is reduced, the intensity of drainage ﬂows also reduces. Regarding the thickness of the drainage ﬂow, it was demarcated at approximately 5 meters, a result that corroborates with what is found in the literature. In this condition, it is also notable that the maximum velocity value is commonly less than 1 m s_1 near the surface. Basically, on nights with drainage runoff, disorderly and unpredictable changes in Wind direction were observed, thus inﬂuencing the formation and duration of these ﬂows. It is also importante to emphasize that the results evidenced for the nights with drainage are exclusively from the data from the Santa Maria experimental site.
Keywords: Engenharia; Camada limite; Atmosfera; Escoamento; Drenagem; Engineering; Boundary layer; Atmosphere; Flow; Drainage; CNPQ::ENGENHARIAS